2019
DOI: 10.1186/s12940-019-0546-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride exposure and sleep patterns among older adolescents in the United States: a cross-sectional study of NHANES 2015–2016

Abstract: BackgroundFluoride from environmental sources accumulates preferentially in the pineal gland which produces melatonin, the hormone that regulates the sleep-wake cycle. However, the effects of fluoride on sleep regulation remain unknown. This population-based study examined whether chronic low-level fluoride exposure is associated with sleep patterns and daytime sleepiness among older adolescents in the United States (US).MethodThis cross-sectional study utilized data from the National Health and Nutrition Exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
2
13
0
Order By: Relevance
“…Given fluoride’s propensity to accumulate in the pineal gland [ 10 , 12 ], along with the well-established relationships of the degree of pineal gland calcification with human melatonin levels [ 16 18 ] and disruption to various sleep-related outcomes (including REM sleep percentage, total sleep time, sleep efficiency, daytime tiredness, and sleep disturbance) [ 18 , 19 ], further research is needed examining the potential for fluoride to impact sleep outcomes. To date, only one study has investigated the association between fluoride exposure and sleep [ 20 ]; none have examined this association in adult humans.…”
Section: Introductionmentioning
confidence: 99%
“…Given fluoride’s propensity to accumulate in the pineal gland [ 10 , 12 ], along with the well-established relationships of the degree of pineal gland calcification with human melatonin levels [ 16 18 ] and disruption to various sleep-related outcomes (including REM sleep percentage, total sleep time, sleep efficiency, daytime tiredness, and sleep disturbance) [ 18 , 19 ], further research is needed examining the potential for fluoride to impact sleep outcomes. To date, only one study has investigated the association between fluoride exposure and sleep [ 20 ]; none have examined this association in adult humans.…”
Section: Introductionmentioning
confidence: 99%
“…The study of fluoride exposure and sleep patterns among a sample of adolescents living in the USA shows that fluoride exposure may be a risk factor for sleep disturbances [130]. The authors found that each 0.52 mg/L increase in tap water fluoride concentration was associated with 1.97 times higher odds of participants reporting snorting, gasping, or stopping breathing while sleeping at night.…”
Section: Sleepmentioning
confidence: 99%
“…Assuming the preferential accumulation of fluoride in the pineal gland and the related possible risk of toxic effects, Malin et al [11] have recently published a study on the processes of sleep regulation among older adults in the United States. They tried to answer the question of whether chronic exposure to low doses of fluoride has an effect on sleep patterns and daytime sleepiness in the studied population.…”
Section: Fluoride Accumulation In the Pineal Gland And Its Consequencesmentioning
confidence: 99%
“…Additionally, adolescents who lived in areas with higher fluoride levels in tap water experienced more frequent daytime sleepiness. The authors [11] were of the opinion that fluoride exposure may contribute to increased pineal gland calcification and subsequent decreases in nighttime melatonin production that contribute to sleep disturbances.…”
Section: Fluoride Accumulation In the Pineal Gland And Its Consequencesmentioning
confidence: 99%
See 1 more Smart Citation